2019
DOI: 10.1371/journal.pone.0224437
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic language dysfunction in systemic lupus erythematosus patients: Results from a single center Italian study

Abstract: BackgroundCognitive impairment (CI) in systemic lupus erythematosus (SLE) is a frequent neuropsychiatric manifestation affecting several domains, even in apparently asymptomatic patients. Current research revealed that the typical CI pattern affects frontal-subcortical circuit and thus executive functions. The impairment of non-literal language or pragmatic language (PL), including metaphors, idioms, inferences or irony has been well described in several conditions such as autism disorders, Parkinson’s disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…SLICC was also associated with cognitive impairment, but only the impairment of neurological domain of the used evaluation tool was independently associated. The association of cognitive impairment with cumulative damage was found by others, [39][40][41] and it is comprehensible that permanent structural damage of the nervous system impairs its functioning.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…SLICC was also associated with cognitive impairment, but only the impairment of neurological domain of the used evaluation tool was independently associated. The association of cognitive impairment with cumulative damage was found by others, [39][40][41] and it is comprehensible that permanent structural damage of the nervous system impairs its functioning.…”
Section: Discussionmentioning
confidence: 84%
“…The MMSE also identified language as another cognitive domain that was weak in this population. Ceccarelli et al 22 found that difficulties associated with pragmatic language were present in more than 50% of their sample. This study suggests that other language components, such as naming, repetition, comprehension, reading, writing, and visual constructive ability, which are evaluated by the MMSE, 13 may also be present.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…6 Furthermore, data from the Sapienza Lupus Cohort identified also the impairment of pragmatic language in SLE patients. 7 The involvement of the fronto-subcortical circuit, the complex DMN network, the development and control of executive functions network and amygdala-hippocampal connections 8 suggested the evaluation of other unexplored fields of research in SLE patients, the so-called emotional intelligence, understood as the ability to reason with emotions to facilitate thinking, and the application of Visual Thinking Strategies Method (VTS). Thus, the present case-control study aims to evaluate emotional intelligence in a monocentric Italian SLE cohort compared to healthy control; secondly, we applied the VTS method in a subgroup of patients, highlighting the possible impact of art in the improvement of cognitive skills, such as critical thinking and problem solving, and quotient and scores obtained in the different areas of emotional intelligence.…”
Section: Introductionmentioning
confidence: 99%